RETHINKING URBAN FAMILY RESILIENCE THROUGH MAQĀṢID AL-SHARĪ‘AH: WOMEN’S ROLE TRANSFORMATION IN GORONTALO - Nurul Mahmudah; Muhammad Syakir Alkautsar; Muhammad Rifqi Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2026)
This study aims to examine how Hulondhalo women, particularly those actively involved in Nahdlatul Ulama (NU) organizations in Gorontalo, interpret and perform their roles in maintaining family resilience amid the dynamics of urban society; how the synergy between Islamic moderation (wasatiyyah), local customs, and the principles of Maqāṣid al-Sharī‘ah shapes family resilience practices; and how NU women negotiate domestic and public roles within the context of social and digital transformation. This study employs a qualitative approach with a phenomenological design conducted in the urban area of Gorontalo, involving key informants consisting of NU women members in Gorontalo City, traditional leaders, and religious leaders selected purposively. Data were collected through in-depth interviews, participatory observation, and documentation, and were subsequently analyzed using the interactive analysis technique of Miles and Huberman through the analytical lenses of Maqāṣid al-Sharī‘ah, local customs, and the principles of wasatiyyah. The findings reveal three major points. First, there is a reinterpretation of the family breadwinner role in which women contribute economically without diminishing the values of family harmony. Second, the strengthening of domestic deliberation (musyawarah) functions as a decision-making mechanism grounded in moderation values. Third, there is an integration between Gorontalo customs and the principles of Maqāṣid in constructing adaptive family norms, including the utilization of digital platforms to reinforce educational and economic family functions. The study also finds that NU women position themselves as guardians of Islamic and cultural values based on the principle of adati hula-hula’a to syar a’, syara’ hula-hula’a to Kitabullah, thereby balancing the demands of modernity with religious values. The originality of this study lies in the formulation of a synthesis framework of adat–Maqāṣid–wasatiyyah as a conceptual model of urban family resilience that is not merely normative, but also contextual and applicable in responding to social, cultural, and digital transformations within urban communities.